The effect of resveratrol on the cryopreservation of Mongolian horse semen - M. Du; M. Du; M. Du; Y. Liu; Y. Liu; Y. Liu; L. Zhang; L. Zhang; L. Zhang; X. Li; X. Li; X. Li; et al. (Archives Animal Breeding)
Cryopreservation of semen has advanced significantly with the development of artificial insemination techniques, but post-thawed sperm often exhibit reduced viability, membrane integrity, and acrosome integrity compared to fresh sperm, leading to decreased fertilization capacity. Oxidative stress is a major concern during cryopreservation. This study investigated the use of resveratrol (RSV), a potent antioxidant, in the cryopreservation of Mongolian horse semen. Different concentrations of RSV were incorporated into semen cryopreservation extenders, and the morphological and antioxidant indices of post-thawed sperm were assessed to determine the optimal RSV concentration. The study also employed tandem mass tag (TMT) quantitative proteomics technology to explore differential proteins and their pathways. The results showed that sperm quality parameters were positively correlated with RSV concentration within a certain range (10–40 µmol L−1) and were significantly higher than the control group. RSV also enhanced the antioxidant capacity of sperm, with the optimal effect observed at 40 µmol L−1. Proteomics analysis identified 10 differential proteins between the control and optimal RSV concentration groups, with 7 upregulated proteins primarily involved in antioxidant activity and maintaining intracellular redox balance. These findings were further validated through real-time fluorescent quantitative PCR and protein immunoblotting, suggesting that RSV has potential as an effective antioxidant for improving the cryopreservation of Mongolian horse semen.